SOSIALISASI EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) SEBAGAI MASKER GEL PEEL OFF - Dewi Kartika; Lulu Atikah; Romauli Anna Teresia Marbun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Fragrant pandans are plants that contain chemical alkaloids, flavonoids, tannins, and polyphenols. Fragrant pandan leaves can be formulated as a gel peel off mask to moisturize the skin. Before formulating fragrant pandan leaves in the extract first and made in several concentrations to see the difference in humidity. 0% (blanko), 2.5%, and 5% are made in 30 gram preparations. Tests performed on preparations include organoleptic tests, homogeneity, pH, dry time preparation, and humidity. Homogeneity test results showed homogeneous preparations, pH in the range of 6.0 that are relatively safe on the surface of the facial skin. The preparation time dries for 30 minutes and meets the drying time requirements. The greater the concentration, the ability to moisturize the skin the better.